Low pressure ion pair chromatography with amperometric detection for the determination of trigonelline in coffee samples. (December 2018) - Sousa, Manuela B.T.; Santos, João Rodrigo; Almeida, P.J.; Rodrigues, J.A.
Abstract: In this work, the use of ion pair chromatography strategy in low pressure chromatographic flow systems is explored for the first time. The straightforward flow manifold encompassed a peristaltic pump, an injection valve and a 1 cm-length C18 monolithic column. The amperometric detection system relied on a boron-doped diamond electrode, used as working electrode. The determination of trigonelline in coffee samples was the case-study selected. This alkaloid is an important quality marker for this commodity and is usually determined using HPLC-UV methodologies. The proposed methodology, based on ion-pair chromatography with amperometric detection, enabled the quantitative resolution of the studied analyte from the matrix compounds by adding to the mobile phase the ion pair reagent, 1-tetradecanosulfonate sodium. The present work, following the recent developments of the low pressure chromatography approach, demonstrates the potentialities of coupling monolithic columns to traditional flow analysis systems for separation and quantification of ionic or ionisable compounds. Graphical abstract: Highlights: Low pressure chromatography in conventional flow analysis systems Ion-pair chromatography and amperometric detection Trigonelline as one of the principal precursors of coffee aroma compounds Exploiting monolithic C18 columns for ionic compounds retention Determination rate of 20 h −1 and acetonitrile waste of 0.2 mL sample −1